Pengaruh Merchandise Terhadap Customer Engagement 504 Slowbar - Senna Satrio; Marina Wardaya (Jurnal Vicidi, 2019)
The purpose of this research is to discover the effect of merchandise produced by 504 Slowbar towards the level of engagement with the customers. The research method used in this research is interview to 3 experts and 3 extremes ( qualitative method, along with questionnaires spread to 50 504 Slowbar Customers. From the research the conclusion that The right merchandise that is suitable with the customer will increase the customer engagement towards the brand 504 Slowbarcan be drawn.